2019
DOI: 10.3389/fnut.2019.00162
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Avenin-Enriched Oat Protein by Chill Precipitation for Feeding Trials in Celiac Disease

Abstract: The safety of oats for people with celiac disease remains unresolved. While oats have attractive nutritional properties that can improve the quality and palatability of the restrictive, low fiber gluten-free diet, rigorous feeding studies to address their safety in celiac disease are needed. Assessing the oat prolamin proteins (avenins) in isolation and controlling for gluten contamination and other oat components such as fiber that can cause non-specific effects and symptoms is crucial. Further, the avenin sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 47 publications
4
22
3
Order By: Relevance
“…4A and 4B. Consistent with the results of Tanner et al [16], the significant 5 -7 bands (peptides) in the range of 20-30 kDa were detected on electrophoretic gels. At 30 kDa where immunoreactive peptides were detected with G12 monoclonal antibody by Comino et al [7], an important difference between two groups of oat genotypes associated with the presence of either a single band or double bands on the gels was detected.…”
Section: Avenin Protein Polymorphism In Immunoreactive Contrast Groups Of Oat Cultivarssupporting
confidence: 89%
See 2 more Smart Citations
“…4A and 4B. Consistent with the results of Tanner et al [16], the significant 5 -7 bands (peptides) in the range of 20-30 kDa were detected on electrophoretic gels. At 30 kDa where immunoreactive peptides were detected with G12 monoclonal antibody by Comino et al [7], an important difference between two groups of oat genotypes associated with the presence of either a single band or double bands on the gels was detected.…”
Section: Avenin Protein Polymorphism In Immunoreactive Contrast Groups Of Oat Cultivarssupporting
confidence: 89%
“…Based on these findings, it should be more correct to speak only about detection of aveninderived epitopes homologous to wheat gliadin 33-mer for whose detection the G12 monoclonal antibody was raised. Moreover, the avenin-derived epitopes determined in the present study do not correspond with avenin-derived epitopes reported to stimulate immune response in CD patients as reported by Tanner et al [16]. It can thus be expected that noncontaminated oat samples with gluten-like immunoreactive peptide levels lower than 20 mg kg -1 will be safer for celiacs than analogous wheat-derived products with the same gluten contents.…”
Section: Contents and Variability Of Immunnoreactive Gluten Peptides In The Set Of Oat Cultivarscontrasting
confidence: 81%
See 1 more Smart Citation
“…28 Nevertheless, numerous studies, based on findings showing that avenins alone do not induce immune responses in most CD patients and symptomatically tolerated by them, point to the safety of adding oats to their diet. [29][30][31][32] In this regard, however, Hardy et al 33 in their in vivo study on 73 biopsy-confirmed HLA-DQ2.5+ CD patients showed that the ingestion of oats (100 g/day) for 3 days mobilizes polyclonal avenin-specific T-cells in blood in fewer than 10% of studied patients. Half of the patients had at least one digestive symptom during this challenge, which was due to a high daily intake of oats (100 g) and a high amount of fiber in them.…”
Section: Introductionmentioning
confidence: 97%
“…In wheat, these proteins are gliadins; in rye, they are secalins; in barley, hordeins, and oats, they are avenins. The phylogenetic relationship between prolamin proteins from different species has been demonstrated with homology comparisons between avenin sequences and α- and γ-gliadins from wheat, B-hordeins from barley, and γ-secalins from rye ( 28 30 ). Herein, we showed that ryegrass has gliadin-like peptides that share a certain level of similarity to avenins and γ-gliadins.…”
Section: Discussionmentioning
confidence: 99%